Spiritual Religious Coping is Associated with Quality of Life in Institutionalized Older Adults - Vitorino, Luciano Magalhães (Journal of religion and health, 2016)
The purpose of this study was to investigate the relationship between spiritual/religious coping (SRCOPE) strategies and quality of life (QoL) in institutionalized older adults. This is a cross-sectional, correlational study, with a sample of 77 older adults in Brazil. The present study found long-term care patients use religious and spiritual coping strategies to deal with their chronic health conditions. Positive SRCOPE and Total SRCOPE have positive correlations with most QoL domains from the WHOQOL-OLD and WHOQOL-BREF. On the other hand, Negative SRCOPE strategies correlated negatively with the facets of “death and dying” from the WHOQOL-OLD. These results suggest the need for an integrative approach for long-term care patients, considering the positive and negative aspects of coping.